Pengembangan E-Modul Berbasis Model Pembelajaran Inkuiri Terbimbing Pada Mata Pelajaran IPAS di Sekolah Dasar - Elvia Maulia; Ramalis Hakim; Alwen Bentri; Darmansyah Darmansyah (Jurnal Penelitian Pendidikan IPA, 2024)
The research was carried out based on facts found in the field regarding the science and science learning process which still lacks teaching materials. The lack of teaching materials or media used in learning causes learning in class to become less active. Apart from that, teachers also do not use learning models that improve students' ability to think critically, which results in students being less active in class. This research uses the ADDIE Model which consists of five steps, namely analysis, design, development, implementation and evaluation. The results obtained from this research are E-Modules based on the Guided Inquiry Learning Model which are valid, practical and effective. The product validity results obtained from three experts, namely media experts, material experts and language experts respectively were 90.38 %; 91.67%; and 100% with a very valid category. In terms of product practicality, the E-Module is in the very practical category with teacher response practicality results of 88.33 % and student response practicality results of 88.35%. The effectiveness results obtained in this research also show that the product developed is very effective for use in the learning process.